The Crisis of Legitimacy in International Trade Law: An Analysis of the Between the United States and China and Its Impact on Third Countries - Mustar Lofi, R (Melayunesia Law, 2025)
This study aims to analyze the crisis of legitimacy in international trade law within the framework of international law, focusing on the U.S.–China trade war and its implications for third countries, particularly Indonesia. The research addresses two main questions: (1) how do violations of international trade law principles manifest in the U.S.–China trade war, and (2) what are the impacts on the economic stability and legal standing of third countries in the global trade system? A normative juridical approach with qualitative analysis was employed, examining legal instruments such as the 1994 GATT and the WTO’s Dispute Settlement Understanding (DSU), supported by empirical trade data. The findings reveal that unilateral actions such as the Section 301 Tariffs and China’s retaliatory measures violated the principles of non- discrimination and Most-Favoured Nation. The trade war illustrates the ineffectiveness of WTO dispute settlement mechanisms and the erosion of compliance by major powers. For countries like Indonesia, the effects include export decline, supply chain disruptions, and investment uncertainty, though opportunities emerge through industrial relocation. The study recommends structural reforms to the WTO system to strengthen the rule of international law, restore legal certainty, and ensure justice in global trade governance amid the rise of protectionist policie.